Five species of the genus Epicephala Meyrick, 1880 (Lepidoptera: Gracillariidae) from China - Li, Houhun; Zhang, Zhenguo (Zootaxa, 2016)
Five species of the genus Epicephala Meyrick, 1880 are reported based on specimens collected from leaves or reared from fruits of different Glochidion plants (Phyllanthaceae) in southern part of China. Epicephala duoplantaria Li, sp. nov., E. daltonii Li, sp. nov., E. jianfenglingina Li, sp. nov. and E. assamica Li, sp. nov. are described as new; E. ancylopa Meyrick, 1918 is redescribed and recorded from China for the first time. Photographs of adults and genital structures are provided.